Transformative Digital Technology for Disruptive Teaching and Learning - Kaliraj, P.; Singaravelu, G.; Devi, T. (CRC Press, 2024)
Generation-Z students are avid gamers and always on social media. Smart like their phones, they must be educated in a smart manner, which involves the use of digital tools. Transformative Digital Technology for Disruptive and Teaching and Learning provides smart education solutions and details ways in which Gen Z learners can be educated. It covers such digital learning strategies as blended learning, flipped learning, mobile learning, and gamification. It examines creative teaching-learning strategies for to encourage modern learners to learn more quickly. The book discusses ways to accelerate the capabilities of teaching and learning transactions. It also covers innovative teaching-and learning processes to meet the challenges of digital learners. Starting with an overview of digital learning resources and processes as well as their advantages and disadvantages, the book then discusses such approaches and strategies as: Learner-oriented and learner-friendly approaches Blended learning Active learning Experiential learning Virtual learning Applications of Cloud computing and Artificial Intelligence Gamification LMS challenges and techno-pedagogical issues for modern As digital technology is disrupting teaching and learning, especially skill development of students in the era of Industry 4.0 and 5.0, this is a timely book. It provides methods, approaches, strategies, and techniques for innovative learning and teaching. It discusses how to leverage new technology to enhance educators' and learners' ability and performance. A comprehensive reference guide for educational researchers and technology developers, the book also helps educators to embrace the digital transformation of teaching and learning